Resources and process performance: today's problems and tomorrow's solutions tomorrow (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The idea behind the principle of procedural economy can be projected both in the individual dimension of each case and in the macro dimension, which concerns the functioning or, to use an expressive foreignism, the performance of the Judiciary, encompassing the way it conducts and resolves the conflicts submitted to it. This last perspective was the one that inspired many of the innovations in the CPC, which is due to come into force in March 2016. From this perspective, which emphasizes the need for the Judiciary to "work well", the aim has been to make each case "yield" more, which means that, when it comes to an end, the underlying controversy has in fact been fully resolved. Of course, one of the main changes that fulfills this purpose is the extension of the authority of res judicata to preliminary rulings.
Keywords: CPC 2015; procedural economy; res judicata; appeal; procedural efficiency